Design and characterization of cellulose nanocrystal-enhanced epoxy hardeners. Issue 4 (1st December 2014) - Peng, Shane X.; Moon, Robert J.; Youngblood, Jeffrey P.
Abstract : Cellulose nanocrystals (CNCs) are renewable, sustainable, and abundant nanomaterial widely used as reinforcing fillers in the field of polymer nanocomposites. In this study, two-part epoxy systems with CNC-enhanced hardeners were fabricated. Three types of hardeners, Jeffamine D400 (JD400), diethylenetriamine (DETA), and (±)-trans-1, 2-diaminocyclohexane (DACH), were evaluated for their compatibility with CNC. The roles of CNC additions and hardener types in epoxy properties were analyzed with tensile testing and dynamic mechanical analysis. The CNC-reinforcing effects on epoxy depended on the structure of hardeners. For example, with less than 2 wt% CNC, Young's modulus was increased by 16% in JD400-cured epoxy and by 19% in DETA-cured epoxy, but had minimal effect for the DACH-cured epoxy. In general, the DETA-cured specimens had the highest increases in mechanical properties among the three hardeners evaluated. These results indicate that CNC additions to pre-formulated hardeners could be an alternative approach for dispersing CNCs within epoxy matrices and for improving the mechanical properties of epoxy. However, residual acetone and water during the curing reaction plasticized the epoxy matrices and must be limited for further property improvements.